A study to evaluate the adequacy of pelvic lymph node coverage in carcinoma cervix patients in Indian population by conventional four field box technique using computerized tomography simulation based pelvic lymph node contouring - Ghosh, Tanmoy; Basu, Joydeep (International Journal of Research in Medical Sciences, 2020)
Background: Traditionally pelvic External Beam Radiotherapy is delivered with four field box technique in carcinoma cervix patients. The primary aim of this prospective observational study is to determine the adequacy of pelvic lymph nodal coverage by conventional Four Field Box Technique with the help of pelvic lymph node contouring by CT simulation. Methods: Between January 2013 and August 2015 sixty patients with biopsy proven Carcinoma Cervix were enrolled in this study. Of these fifty-three patients were available for final analysis. CT simulation based Pelvic lymph node contouring was done for each patient. Then two External Beam Radiotherapy plans were generated, one contoured based and the other based on bony landmark based Four Field Box Technique. The number of patients whose contoured lymph nodes lies partly outside the field borders of the bony landmark-based plan and also its extent was determined. D90 of various groups of pelvic lymph nodes obtained from both the plans were compared using ‘paired sample t - test’. Results: It was seen that with Four Field Box Technique there is inadequate coverage of common iliac lymph nodes in 34/53 patients. The difference between the mean D90 of common iliac lymph nodes in two sets of plans was found to be statistically significant. Conclusions: Pelvic field planning should be individualized. CT simulation-based radiotherapy planning should be done for each individual patient to adequately cover the nodal microscopic disease.